TRANSLATION PROCEDURE OF CULTURE SPECIFIC TERMS FOUND ON BOOK BAHASA INGGRIS UNTUK PEMANDU WISATA - Ni Made Likhita Ananda; Ni Nyoman Tri Sukarsih; Ni Made Diana Erfiani (LPPM Universitas Dhyana Pura, 2023)
This study aims to analyzes the translation procedures and culture in specific terms intranslating a book Bahasa Inggris Untuk Pemandu Wisata. The strategy of translation divided intoprocedure and method this study only discuss Procedure and Culture in specific terms (Newmark,1988). This study approach a qualitative methods and the data was taken from the book BahasaInggris Untuk Pemandu Wisata (Dewi et al., 2019), The data collected by Observation, note takingand non participation interview, from english as a source language (SL) into bahasa indonesia as atarget language (TL), the results source there were, transference 17.39%, naturalization 21.73%,cultural equivalence 4.35%, functional 2.17%, descriptive equivalence 6.53%, synonymy 6.53%,through translation 4.35%, transposition 28.26%, recognize translation 4.35%, couplets 4.35% oftotal 46 data and result of culture categories in data analyzed include ecologi 25%, material culture35%, socio-cultural 15%, organizations, traditions, activities, and concepts 15% Finally, thecategory of movements and habits 10%, In conclusion, the result show that this book contains alot of transposition translation procedures seen from the results with the highest percentage about28.26% and contains cultural terms related to food, clothing, houses, cities, and transportationseen from the highest percentage of results in the material culture category which is 35%.